Some of the purposes of the Abbasid poetry of Bashar bin Burd and Abu Tammam: )a comparative study( (Journal of Human Sciences, 2024)
The research in the theoretical section aimed to talk about poetic purposes in the first Abbasid era in general, and in the applied section it was concerned with studying some poetic purposes in the poetry of (Bashar bin Burd and Abu Tammam) in particular by balancing them. Especially since they are considered among the great poets of the first Abbasid era, and they both belong to a poetic school that differs from the other. The poet (Bashar bin Burd 96-168 AH) is considered one of the first modern or new poets in Abbasid poetry. His poetry ranged between imitation and renewal, so he was imitated in praising And again in satire, pride, and ghazal. As for the poet (Abu Tammam 180-228 AH), he was one of the poets of the third class of hadith scholars. However, we find that he was imitative in some of his purposes and innovative in others. He was even called the poet of craftsmanship due to his excessive use of beautiful embellishments and innovative meanings. The research relied on the descriptive analytical method, with the help of the historical method. The descriptive analytical approach is concerned with extrapolating texts, analyzing them, interpreting them, and then showing the differences between them, by reviewing each purpose of poetry and its interpretation by the two Abbasid poets (Bashar bin Burd and Abu Tammam), and determining the ways they dealt with it. The study also reached the following results: Poetry expresses the life of an individual. Poetry is close to the psyche of its owner. It is a means of expressing what occupies his mind and senses; Although it is his source of livelihood in many cases; He did not spare himself to spread his joys and sorrows. The study concluded  use of poets the mastery of stylistic craftsmanship, as they made extensive use of Badi’ with its various types of counterpoint, alliteration, assonance, contrast, and other Badi’ arts. The trends and inclinations of the poets varied, some of them took the mental direction; Or creative, nature photography, or self-expression; Or asceticism, or philosophy.